BRIDGING CULTURES: THE IMPACT OF BAHASA INDONESIA ON INTERNATIONAL LEGAL DIPLOMACY - Sudarsana, I Wayan Alit; Manual Selvaraj Bexci (PT. Jurnal Center Indonesia Publisher, 2025)
This research explores the role of Bahasa Indonesia in shaping international legal diplomacy through a doctrinal legal analysis. By examining primary legal sources, such as treaties, diplomatic correspondences, and international agreements involving Indonesia, alongside secondary sources including scholarly articles, legal commentaries, and historical analyses, this study aims to uncover how Bahasa Indonesia functions as a diplomatic tool in legal contexts. The research critically analyses the extent to which language can bridge cultural and legal divides, enhance mutual understanding, and influence the negotiation and interpretation of international agreements. By situating Bahasa Indonesia within broader legal and diplomatic frameworks, this study offers insights into the intersection of language, culture, and law on the global stage, highlighting the strategic importance of linguistic identity in international legal diplomacy.